The Constellation of Meaning of Mahabbah and Raghiba in the Qur'an: A Semantic Analysis by Toshihiko Izutsu - Faradiella, Elvynanda; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Vocabulary in the Quran is a word that has an important role in determining the conceptual arrangement of the worldview standards for the meaning of the Quran. Semantics is a term for the study of the analysis of the science of the Quran and the study of the meaning of a word in a language that, according to Toshihiko Izutsu, is studied by looking for the basic meaning, rational meaning, synchronic and diachronic, as well as the weltanschauung of the word in the Quran. From the word mahabbah, we can see that he is talking about Allah's love for His servants, servants of Allah, fellow creatures, and also the worldly. Meanwhile, Raghiba tends to feel like belonging to a creature. The analysis of this article will discuss how the concepts of mahabbah and raghiba are related to the concept of the meaning of the Quran further. Therefore, the author wants to study the "Constellation of the Meanings of Mahabbah and Raghiba in the Al-Quran (Semantic Study of Toshihiko Izutsu)".